Paintball-related traumatic liver injury. (27th April 2016) - Luck, Joshua; Bell, Daniel; Bashir, Gareth
Abstract : Paintball is a popular recreational sport played at both amateur and professional level. Ocular injuries are well recognised, although there is a growing body of literature documenting superficial vascular as well as deep solid organ injuries. An 18-year-old man presented with signs and symptoms consistent with acute appendicitis. Intraoperatively, a grade III liver injury was identified and packed before a relook at 48 h. No further active bleeding was identified; however, follow-up ultrasound at 3 weeks demonstrated non-resolution of a large subcapsular haematoma. The patient was readmitted for a short period of observation and discharged with repeat ultrasound scheduled for 3 months. This represents the first report of paintball-related blunt traumatic injury to the liver. Solid organ injuries of this nature have only been reported three times previously—all in the urological setting. This case also highlights issues surrounding the use of routine follow-up imaging in blunt liver trauma and provides a concise discussion of the relevant literature.